A Glance Into Healthcare Delivery During COVID-19 Pandemic: A Survey Among Turkish Medical Doctors - Karaman, Irem; Ildir, Selin; Ozkaya, Sevket (Frontiers in Medicine, 2022)
The coronavirus 2019 (COVID-19) pandemic had an enormous impact on healthcare delivery globally. We conducted a cross-sectional online survey in Turkey to evaluate the impact of COVID-19 on healthcare services in Turkey. A 35-item anonymized online survey was completed by HCPs (medical doctors, MD) who continued their clinical practice during the COVID-19 pandemic in Turkey, regardless of their specialties or degrees. Overall, 209 HCPs participated in the study. Forty-two percent of the participants stated that their current workload intensity has been increased compared with the pre-pandemic era. More than half of the participants (54.6%) were using telemedicine services during their clinical practice, however, the effectiveness of telemedicine for first-time patients and follow-up patients was rated as low. The majority of participants (59.3%) reported that during the peak period of the pandemic, they encountered only a small variety of cases, other than COVID-19. Fifty-two percent of the participants agreed that they occasionally had patients who received misdiagnosis in the first admission due to the suspicion of a possible COVID-19 infection predominating the diagnostic process (eg. not excluding COVID-19 even though the PCR test is negative). For the distribution of possible late-diagnosed diseases, 25.8% of HCPs selected chest diseases, followed by infectious diseases, heart diseases, and cancer. In general, participants agreed that there was an increase in the negligence in the follow-up of various diseases and/or complication rates due to COVID-19 pandemic. Sixty percent of the HCPs agreed that HCPs are being much more rigorous to diagnose/treating COVID-19 than other important diseases. Fifty-seven percent of the participants stated that the diagnosis and follow-up of chronic diseases are affected, while 57.9% of the HCPs stated that some diseases that show similar signs and symptoms as COVID-19 are not diagnosed correctly during COVID-19 pandemic. Findings from this study emphasize that COVID-19 pandemic has significantly caused delayed diagnoses and interruption in the management of chronic diseases, and also increased the risk of missing out the diagnosis of non-COVID-19 diseases. The study genuinely aims to yield the floor to a permanent improvement in post-pandemic clinical management by a focused approach in distinct areas of medical care.